2015
DOI: 10.1016/j.tranon.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-MEK1/2 and uPAR Expression Determine Sensitivity of AML Blasts to a Urokinase-Activated Anthrax Lethal Toxin (PrAgU2/LF)

Abstract: In this study, we attempt to target both the urokinase plasminogen activator and the mitogen-activated protein kinase pathway in acute myeloid leukemia (AML) cell lines and primary AML blasts using PrAgU2/LF, a urokinase-activated anthrax lethal toxin. PrAgU2/LF was cytotoxic to five out of nine AML cell lines. Cytotoxicity of PrAgU2/LF appeared to be nonapoptotic and was associated with MAPK activation and urokinase activity because all the PrAgU2/LF-sensitive cell lines showed both uPAR expression and high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…AML is associated with poor long-term survival, even with newer chemotherapeutic agents. Various studies reported that AML relapse and resistance to chemotherapies may originate from a small clone, known as Leukemic Stem Cells (LSCs) [ 1 ]. LSCs are identified as a chemo-resistant clone that has the ability for limitless self-renewal and also production of a large number of blast cells [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…AML is associated with poor long-term survival, even with newer chemotherapeutic agents. Various studies reported that AML relapse and resistance to chemotherapies may originate from a small clone, known as Leukemic Stem Cells (LSCs) [ 1 ]. LSCs are identified as a chemo-resistant clone that has the ability for limitless self-renewal and also production of a large number of blast cells [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main strategy for treatment is using chemotherapy. Although many different clinical antitumor agents are currently used in the treatment of acute promyelocytic leukemia (APL), acute myeloid leukemia (AML), or CML patients, a high proportion of these leukemic patients eventually relapse [31][32][33]. Hence, alternative approaches…”
Section: Introductionmentioning
confidence: 99%
“…LeTx is a binary toxin composed of two proteins: PA And LF. LF is a zinc-activated metalloprotease that inhibits the MAPK pathway by cleaving MEKs (35,36). Based on the ability of LeTx to cause cell death or inhibition of migration and invasion due to MAPK inhibition, breast cancer cells were treated with LeTx, and the migratory and invasive capabilities of the cells were examined in the present study.…”
Section: Discussionmentioning
confidence: 99%